Understanding work-related intentions using the theory of planned behaviour: a systematic review - Yeoh, Jie Ru; Hanif Farhan Mohd Rasdi,; Dzalani Harun,; Shahirah Md Rasid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Work can guarantee financial stability and quality of life, foster identity and self-confidence and ensure social well being. Thus, it is vital to understand the motivation and intention to work. The theory of planned behaviour (TPB) has been used extensively in theory and research in a wide range of human behaviours. However, research on the efficacy of the TPB in the vocational realm remains limited. This study aims to review the applications of the TPB in work-related intention. Relevant studies were systematically searched using standardised keywords across two databases. Three hundred and sixty-six research articles (n=366) were identified, however, only seven articles (n=7) were eligible to be evaluated in this study using the Assessment for Cross-Sectional Studies (AXIS) tool. All studies confirmed the efficacy of the TPB in explaining work intentions. The explained variance in intention varied from 10% (post-retirement work intention) to 59% (to work with older adults). However, the underlying core constructs of TPB namely attitudes, subjective norms, and perceived behavioural control (PBC) do not always altogether consistently predict the intention to work. Besides, few review studies have reported variables that are not included in TPB, such as moral obligation, identity, and tenure, which contributed to a significant amount of variance in intention. Overall, the findings of this review indicated that TPB is helpful in understanding work intention. However, further investigation is needed to estimate the extended variables’ performance in explaining intentions and to cover a broader aspect of work intentions.